2012
DOI: 10.1155/2012/569040
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody with Cross-Reactivity between Insulin and Ductal Cells May Cause Diabetic Mastopathy: A Case Study

Abstract: Lymphocytic mastopathy or diabetic mastopathy is a benign breast disease characterized by dense fibrosis, lobular atrophy, and aggregates of lymphocytes in a periductal and perilobular distribution. The condition usually affects women with a long history of diabetes mellitus (DM) and also those with autoimmune disorders. While the pathogenesis is unknown, a particular type of class II human leukocyte antigen has been associated with this disease. Herein, we report a case of diabetic mastopathy which clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…At least, mammary duct self-antigens may exhibit a cross-reactivity towards other autoantibodies. This mechanism has already been described in a long-lasting Type 2 diabetic patient treated with insulin, in whom anti-insulin autoantibodies cross-reacted with breast ductal epithelium, leading to ductitis and mastitis [30]. This mechanism of cross reactivity could also be involved in the cases of concomitant breast cancer and vasculitis [167,168].…”
Section: The Role Of Mammary Epithelial Cellsmentioning
confidence: 84%
See 1 more Smart Citation
“…At least, mammary duct self-antigens may exhibit a cross-reactivity towards other autoantibodies. This mechanism has already been described in a long-lasting Type 2 diabetic patient treated with insulin, in whom anti-insulin autoantibodies cross-reacted with breast ductal epithelium, leading to ductitis and mastitis [30]. This mechanism of cross reactivity could also be involved in the cases of concomitant breast cancer and vasculitis [167,168].…”
Section: The Role Of Mammary Epithelial Cellsmentioning
confidence: 84%
“…Miura and coll. described one case of lymphocytic mastopathy in a patient with a 31-year history of Type 2 diabetes [30] and demonstrated the presence of circulating anti-insulin autoantibodies with cross-reactivity towards breast duct epithelium. Such autoantibodies might be linked to the onset of inflammation within the breast tissue and trigger clinical mastitis flares.…”
Section: Diabetesmentioning
confidence: 98%
“…In addition, it is also believed that diabetic mastopathy, such as diabetic nephropathy and retinopathy, should be regarded as a chronic complication of diabetes[ 12 ]. Miura et al [ 13 ] reported an elderly female patient whose autoantibodies in serum reacted positively against her ductal epithelium as well as other diabetic and nondiabetic breast ductal cells. The results of the insulin antigen absorption test showed a decreasing insulin concentration with the increasing antigen absorption intensity.…”
Section: Discussionmentioning
confidence: 99%
“…There are several proposed inflammatory stimuli, including glycosylated native collagen in the breast parenchyma [7], deposition of glycosylated end products that act as neoantigens [6, 11], underlying autoimmune disease [1, 12], antibody cross-reactivity to exogenous insulin [13] or insulin contaminants [14], and altered tissue degradation due to locoregional cytokine imbalances [6, 7]. While debate continues about the inciting stimulus, the remaining pathophysiologic mechanisms are better understood.…”
Section: Discussionmentioning
confidence: 99%